Methods of Teaching Exact and Natural Sciences Using Computer Technologies to Agricultural Students - Hilola Odiljon Qizi, Abdusamatova; Aysholpan Tejetdinovna, Shamishova; Mavluda Ibrayimovna, Xudoyberdieva; Dilmurod Egamberdiyevich, Abdurahmonov; Asadullo Izzatulloevich, Ochilov (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the new computer technologies in the agricultural lesson. Today we are living in the technology century. We can not imagine our lives without computers and the internet.